Building an Optical Free-Electron Laser in the Traveling-Wave Thomson-Scattering Geometry - Steiniger, Klaus; Albach, Daniel; Bussmann, Michael; Loeser, Markus; Pausch, Richard; Röser, Fabian; Schramm, Ulrich; Siebold, Mathias; Debus, Alexander (Frontiers in Physics, 2019)
We show how optical free-electron lasers and enhanced incoherent Thomson scattering radiation sources can be realized with Traveling-Wave Thomson-Scattering (TWTS) today. Emphasis is put on the realization of optical free-electron lasers (OFELs) with existing state-of-the-art technology for laser systems and electron accelerators. The conceptual design of optical setups for the preparation of laser pulses suitable for TWTS OFELs and enhanced Thomson sources is presented. We further provide expressions to estimate the acceptable alignment tolerances of optical components for TWTS OFEL operation. Examples of TWTS OFELs radiating at 100 nm, 13.5 nm and 1.5 Å as well as an incoherent source producing 30 keV photons highlight the feasibility of the concept and detail the procedure to determine the optical components parameters of a TWTS setup.